Praksis pendidikan multikultural di SDN 2 Tonusu Kabupaten Poso - Nashrullah, Nashrullah; Lagandesa, Yun Ratna; Hariana, Kadek; Lapasere, Sisriawan (COLLASE (Creative of Learning Students Elementary Education), 2024)
This research aims to describe the practice of multicultural education at SDN Tonusu, Poso Regency. This research is qualitative research. The subjects in this research were the principal, teachers and students of SDN 2 Tonusu. Data collection methods through in-depth interviews, observation and documentation studies. The results of this research show that 1) formally the school community's understanding of multicultural education is still at the level of translational understanding, but substantively it has become part of educational activities so that school institutions have the potential to become more inclusive; 2) The school community's awareness of multicultural values ​​and attitudes comes from cultural and religious values. The school community constructs that these two sources of multicultural values ​​are not in conflict with each other but instead complement each other; 3) The pattern of implementing multicultural education at SDN 2 Tonusu is linear, successively exploring values, socialization and praxis. However, it also follows an open implementation pattern, meaning giving autonomy to school institutions to interpret and develop the concept of multicultural education in accordance with the character of the school institution. Keyword: multicultural education, elementary school